Therapeutic potential of Baicalin against experimental obsessive compulsive disorder: Evidence from CSF, blood plasma, and brain analysis - Dhiman, Abhinay; Choudhary, Divya; Mehan, Sidharth; Maurya, Pankaj Kumar; Sharma, Arun Kumar; Kumar, Aakash; Mukherjee, Ritam; Gupta, Sumedha; Khan, Zuber; Gupta, Ghanshyam Das; Narula, Acharan S. (Journal of neuroimmunology, 2025)
Obsessive-Compulsive Disorder (OCD) is a complex neuropsychiatric condition characterized by recurrent obsessions and compulsions, significantly impacting an individual's functionality and quality of life. This study aimed to explore the neuroprotective and therapeutic potential of baicalin, a flavonoid with known antioxidant, anti-inflammatory, and neurotropic properties, in an animal model of OCD induced by 8-OH-DPAT (8HPAT). The research utilized in silico docking studies and in vivo experiments to assess baicalin's interactions with key intracellular targets: SIRT-1, Nrf2, HO-1, and PPAR-gamma, and its effects on neurochemical, neurobehavioral, and histopathological parameters. In silico results indicated a strong binding affinity of baicalin for SIRT-1, Nrf2, HO-1, and PPAR-gamma, suggesting potential regulatory roles in antioxidant and anti-inflammatory pathways. In-vivo findings demonstrated that baicalin, administered at doses of 50 mg/kg and 100 mg/kg, significantly alleviated OCD-like behaviours, including excessive lever pressing, marble burying, and compulsive checking. Baicalin treatment normalized serotonin and dopamine levels and reduced glutamate levels in the brain, restoring neurotransmitter balance. Furthermore, baicalin decreased inflammatory cytokines (TNF-alpha and IL-1 beta), improved complete blood count profile, and gross morphological and histopathological alterations by restoring neuronal density and cellular integrity in affected brain regions. Combining baicalin with fluvoxamine (10 mg/kg) showed synergistic effects, further enhancing neuroprotective outcomes. These results suggest that baicalin holds promise as a potential therapeutic agent for OCD, warranting further clinical investigation to explore its efficacy and underlying mechanisms in human subjects. The findings underscore the importance of targeting intracellular pathways and neurotransmitter systems in developing effective treatments for OCD and related neuropsychiatric disorders. [Display omitted] •Baicalin (BAC) selectively activates SIRT-1, Nrf2, HO-1, and PPAR-gamma signaling neuronal pathways in experimental OCD.•BAC alleviates OCD-like behaviours and modulates neurotransmitter levels.•BAC reduced inflammatory cytokines, gross morphological and histopathological alterations in various brain regions.•BAC combined with fluvoxamine enhanced neuroprotective effects, suggesting synergistic benefits.